Shifting trends in interior design careers: the graduates' story 1977 to 1998 - Marina Lommerse (1999)
Introduction/Background - This study is a retrospective investigation of the career paths/patterns of interior designers over a 21-year period, between 1977 and 1998. The aim of the study was to document major influences and trends in their career development. In particular, the effects of global changes that contributed to career change were examined. It is important that educational institutions prepare new graduates for the reality of the rapidly changing workplace, while providing experienced design practitioners and post-graduates with research that may increase their understanding of careers possible with an Interior Design education. Research Design - Little documented research exists concerning the career development patterns of graduate Interior Designers/Architects. Thus, this applied research project was designed to contribute new knowledge in this important area. The research and analysis was primarily a qualitative/interpretive use of life history, supplemented by a survey questionnaire that was used to gather preliminary qualitative information from a comparative sample of Canadian and Australian interior design graduates. Key Findings - Seventeen trends in career development were identified, confirming the importance of the "building block" years-one to five. Additionally, as global change affects careers significantly, the need for career counselling in the profession was confirmed.